Les fours de tuiliers gallo-romains - Le Ny, Françoise (Éditions de la Maison des sciences de l’homme, 2022)
Based on the author’s Master’s dissertation, this study deals with Gallo-Roman building materials made from fired clay : particular attention is paid to the firing stage in the production of these materials. The author’s inventory of 142 identified tile factories in France has enabled her to provide new information on kiln technology, to establish a typology and to propose a possible chronological sequence. Although work of this kind has been carried out in Great Britain, a similar study had not been done for France. F. Le Ny’s timely remedy to this problem casts light upon an industry which has seldom been studied. The author is currently working on a doctoral thesis in archaeological science at the University of Rennes I.